PENGARUH RISIKO KREDIT RISIKO OPERASIONAL DAN RISIKO LIKUIDITAS TERHADAP PROFITABILITAS BPR DI KOTA DENPASAR - Capriani, Ni Wayan Wita; Dana, I Made (E-Jurnal Manajemen, 2016)
Profitability is the ability of banks to make profits for a certain period . The amount of the profitability of a company tend to be influenced by various risks. Risks that occur will cause a loss for the bank if not detected and not well managed. The purpose of this study is to determine the effect of credit risk, operational risk, and liquidity risk to profitability BPR in Denpasar 2010-2014. This research was conducted in rural banks ( BPR ) contained in Denpasar 2010-2014. The number of samples taken is as much as 10 BPR , through purposive sampling technique. The data collection method used is non- participant observation method with data analysis technique multiple linear regression. Based on the analysis found that credit risk is not significant  positive  effect on profitability. Operational risk is a significant negative effect on profitability. Liquidity risk is a significant positive effect on profitability.
Keywords: risiko kredit; risiko operasional; risiko likuiditas; profitabilitas; NPL; BOPO; LDR; ROA